ENGLISH INFLECTIONAL ERRORS MADE BY INDONESIAN DEAF PEOPLE IN WRITING COMPOSITION - Suwandi Suwandi; Deliana Deliana; Desri Maria Sumbayak (Universitas Islam Sumatera Utara (UISU), 2021)
This paper was conducted to describe the types of English inflectional errors found in Indonesian deaf people in writing composition, identify the sources of the errors in the use of English inflection, and to find out the percentages. The Indonesian deaf people were from Indonesian deaf community groups on Facebook, WhatsApp, and Instagram. This research used a descriptive qualitative approach by applying English inflection theory by Andrew Carstairs-McCarthy. The data collection techniques were conducted by using an online English writing test. The results showed that there were 179 errors in total in Indonesian deaf people’s writings. The most found error was in Third Person Singular Present Inflection with 51 errors (28.5%) and the least was in Present Participle Inflection with 16 errors (9%), and the rest were 18 errors (10%) in Preterite Inflection, 19 errors (10.6%) in Comparative Inflection, 22 errors (12.3%) in Superlative Inflection, 27 errors (15.1%) in Past Participle Inflection, and 26 errors (14.5%) in Plural Inflection. The source of error was Intralingual Error with 156 errors (87.15%) (False Concept Hypothesized with 6 errors (3.3%), Incomplete Application of Rules with 8 errors (4.5%), Overgeneralization with 23 errors (12.85%), and Ignorance of Rules Restriction with 119 errors (66.5%)) and Interlingual Error with 23 errors (12.85%).